Efficacy of solid dispersion of fenbendazole against gastrointestinal strongylatosis of young cattle - A. I. Varlamova; I. A. Arkhipov; K. M. Sadov; S. S. Khalikov; M. V. Arisov; E. N. Borzunov (Российский паразитологический журнал, 2021)
The purpose of the research is to study the efficacy of solid dispersion of fenbendazole (SDF) against nematodoses of young cattle.Materials and methods. The study of SDF, obtained by mechanochemical processing of fenbendazole substance with polyvinylpyrrolidone (PVP) polymer, was carried out on 126 young cattle naturally infected with nematodiroses and other gastrointestinal strongylatoses. The animals were divided into 6 experimental groups of 10–11 animals each and SDF was administered once orally at doses of 2.0; 3.0 and 4.0 mg/kg of active substance (a.s.) (I-III groups) in comparison with the mechanical mixture of fenbendazole (FBZ) and PVP in a ratio of 1:9 (IV group) and substance FBZ at a dose of 3.0 mg/kg (group V) against each helminthosis. The control group of animals did not receive the drugs. Anthelmintic efficacy was evaluated in the "control test" based on the data of ovoscopic examination of feces of young cattle by flotation method before and 17 days after drugs administration.Results and discussion. SDF with PVP at a dose of 2.0; 3.0 and 4.0 mg/kg of a.s. in the form of a 10% powder showed respectively 88.4; 97.3 and 100% efficiency at nematodiroses and 89.2; 98.4 and 99.5 % activity against other types of gastrointestinal strongylates upon obtaining 32.3 and 32.4 % effect of the mechanical mixture of FBZ with PVP and 29.7 and 27.4% efficiency of the base preparation at a dose of 3.0 mg/kg. SDF showed 88.4; 97.3 and 100% of efficacy at doses of 2.0; 3.0 and 4.0 mg/kg of a.s., respectively, against nematodiroses and 89.2; 98.4 and 99.5% against other gastrointestinal strongylatoses in the form of 10% powder. It should be noted that mechanical mixture of PBZ with PVP showed 32.3 and 32.4% efficacy and the efficacy of the basic drug was 29.7 and 27.4% at a dose of 3.0 mg/kg against each helminthosis.